Perlindungan Hukum Debitur Terhadap Fintech Berbasis Aplikasi Yang Tidak Terdaftar Di Otoritas Jasa Keuangan Provinsi Riau - Melly Carolina Bangun; Hayatul Ismi; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The development of the digital era of technology in Indonesia is very rapid nowadays, which affects people to be able to access the latest information, and makes it easier for people to complete their work quickly and effectively with the availability of electronic service features. One of the technological developments that has become a trending topic in Indonesia today is Financial Technology (FinTech). In banking itself, it has adopted Financial Technology, which digital banking consists of (Internet Banking, M_Bangking, SMS banking, Phone Banking, and ATM). However, over time, many FinTech Start-Ups have sprung up that offer various conveniences to the public that put banking at risk.This type of research is a sociological juridical research, because the author examines the problems that occur. The research was conducted at the Financial Services Authority of Riau Province, while the population and sample were all parties related to the problems studied in this study, the data sources used, primary data, secondary data and tertiary data, data collection techniques in this study were carried out by interviews. and literature review.Based on the role of the financial services Authority (OJK) in providing legal protection for online loan recipients. With the victims of online loans who don't know what they have to do to get their rights. The OJK Regulation states how the role of the OJK is in providing information, education and also complaint services for people experiencing problems in the banking sector and also in fintech. The thing that makes the author interested in knowing how the role of the Financial Services Authority (OJK) in providing legal protection for online loan recipients is not registered in an online-based loan and borrowing agreement according to the Financial Services Authority Regulation Number 77 / POJK.01 / 2016 regarding lending and borrowing money services based on information technology (OJK Riau Province case study).From the results of research conducted by the author at the Financial Services Authority (OJK) in providing legal protection for illegal online loan recipients in the Online-Based Lending and Borrowing Agreement. Here the role of the OJK is not really felt by its presence in the community regarding information and education by disseminating it to the public about fintech. In the OJK Regulation it is stated that OJK is in charge of providing information, education to the public and providing complaint services to the public. In addition, OJK has also not made a regulation whereby an organizer or lender cannot operate without obtaining a license or permit from the OJK, considering that there are many illegal operators who have not obtained OJK's license but are already operating.Keywords: Financial Technology –Legal Protection – Ilegal Online